2022
DOI: 10.1155/2022/8430489
|View full text |Cite
|
Sign up to set email alerts
|

Ethnozoological Study of Traditional Medicinal Animal Parts and Products Used among Indigenous People of Assosa District, Benishangul-Gumuz, Western Ethiopia

Abstract: Traditional medicine is a global practice and depends on locally available natural resources and indigenous knowledge. Animals and their products have been used in the preparation of traditional remedies in various cultures since time immemorial. This study aimed to identify and document traditional medicinal sources from animals and associated indigenous knowledge in Assosa Districts, Benshangul Gumuz region, western Ethiopia, from September 2019 to July 2020 to ensure sustainable utilization of natural resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…People use these parts for traditional medicine because it has been passed down from generation to generation from their ancestors. According to Kumera et al (2022), traditional medicine is a practice carried out by the community depending on locally available natural resources and indigenous knowledge since ancient times. The results of previous research reported that people in Northern Ethiopia use animal parts such as urine, bile, stomach, milk, whole animals, feces, pancreas, honey, meat, lips, blood, buttocks, and hair (Yirga et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…People use these parts for traditional medicine because it has been passed down from generation to generation from their ancestors. According to Kumera et al (2022), traditional medicine is a practice carried out by the community depending on locally available natural resources and indigenous knowledge since ancient times. The results of previous research reported that people in Northern Ethiopia use animal parts such as urine, bile, stomach, milk, whole animals, feces, pancreas, honey, meat, lips, blood, buttocks, and hair (Yirga et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Traditional medicine is the total of knowledge, skills, and practices based on the theories, beliefs, and experiences indigenous to different cultures, that are used to maintain health, as well as to prevent, diagnose, and treat various illnesses. 1 Medicinal plants are claimed to possess antibiotic properties and are also used comprehensively by tribal people worldwide. They have been known to alleviate various diseases in traditional medicine.…”
Section: Introductionmentioning
confidence: 99%
“…wildlife harvesting to support their livelihoods (Brashares et al, 2014). The harvest of wildlife and wildlife products is an important component of rural and Indigenous people's nutritional (e.g., Kuhnlein et al, 2008;Haq et al, 2022) and cultural (e.g., Ngoufo et al, 2014;Kumera et al, 2022) identities and have proven to be sustainable, even ecologically beneficial (e.g., Bodmer et al, 2020). The persistence of traditional subsistence socio-ecological systems has been jeopardized by conservation-related injustices, such as the criminalization of subsistence hunting, that disproportionately affect Indigenous peoples and local communities (see van Vliet et al, 2015;Vlasova et al, 2017).…”
mentioning
confidence: 99%